Claiming social security benefits early : analysis, issues, and health coverage options - Walton, Ricky H. (Health care issues, costs, and access., 2014)
Deciding when to retire and claim Social Security benefits can be one of the most important financial decisions older Americans make. Despite higher monthly benefits for those who delay, many people still claim Social Security retirement benefits at age 62, the earliest age of eligibility. In 2014, these early claimers will see their monthly benefits reduced by 25 percent compared to what they would have received if they had delayed claiming until age 66, the current full retirement age. At the same time, some early claimers do not have access to government or employer-sponsored health insuran.